Alfred Raquez and the French experience of the Far East, 1898-1906 - Gibson, William, 1974- author.
1 online resource.
Keywords: "A study of an enigmatic travel writer and his work in colonial Asia during the fin de siècle. In 1898, a man calling himself Alfred Raquez appeared in Indochina claiming to be a writer travelling the world to escape unfathomable sorrows back home in France. He published thousands of pages of highly detailed travel accounts that open a unique window onto the European presence in the Far East. He travelled far into the Zomia of upland Southeast Asia, a peripheral zone populated by people who lived beyond official state power. Raquez explored the nightlife of Shanghai and operated a popular cabaret in Hanoi. An amateur anthropologist, he helped mount expositions of colonial material in Hanoi and Marseille. Raquez met people in the highest circles of Belle Époque Indochina, as well as the kings of Annam, Cambodia, Laos and Siam. And yet, despite the charm and the ebullience and the erudition, through all his travels and rising fame, the man kept a secret that was so mortifying that even his closest companions would not learn of it until after his death in 1907. In truth, Alfred Raquez did not exist. A fascinating read for students and scholars of colonial Southeast Asia, and European colonialism more broadly"--